Ghost of a potion - Blake, Heather (Blake, Heather. Magic potion mystery., 2015)
When her boyfriend's mother is accused of killing architect Haywood Dodd during a costume ball, shop owner Carly Beth Hartwell employs her keen skills of detection to clear her name while dealing with a group of ghosts who need her help, including the deceased. --Publisher